Networking, Leadership, Empowerment - Calliess, I. T.; Rojnic Kuzman, M.; Treichel, K.; Nikitopoulos, J.; Malik, A. (Die Psychiatrie, 2009)
As society’s expectations of mental health professional change radically, educational programs and policies need to keep pace with this change. Trainees and young psychiatrists have established their distinct identity and assured that educational policies are reformed to create competent mental health professionals who are fit for purpose in tomorrow’s world. In order for this to happen, it has taken over a decade of dedication, hard work and motivation from past and present psychiatric trainees and young psychiatrists to travel the journey from having a vision of an international network to develop the existing highly structured network. Networking and empowerment facilitated by national and international young psychiatrists’ organizations has allowed young psychiatrists to participate in decision-making processes and create frameworks for their own professional development. This paper outlines the principles and objectives that underpin the existing networks of national and international young psychiatrists’ organizations. It also describes the various educational and networking activities undertaken by these organizations and uses the case study from Croatia to describe the role of these networks in the formation of national associations of young psychiatrists and trainees.Mit den sich radikal verändernden gesellschaftlichen Erwartungen an das psychiatrisch-psychotherapeutische Versorgungssystem und seine professionellen Vertreter müssen auch Weiterbildungsprogramme und -konzepte Schritt halten. Psychiatrische Weiterbildungsassistenten und junge Fachärzte haben mittlerweile eine wahrnehmbare Identität entwickelt und Reformprozesse innerhalb der psychiatrischen Weiterbildung unterstützt, damit auch in Zukunft Psychiater im Hinblick auf die neuen gesellschaftlichen Rahmenbedingungen kompetent ausgebildet werden. Es hat über ein Jahrzehnt harter Arbeit, Motivation und Engagement von ehemaligen und gegenwärtigen Weiterbildungsassistenten und jungen Fachärzten gebraucht, um von der Vision eines internationalen Netzwerkes zu einem existierenden und hoch-strukturierten Interessenverbund zu gelangen. Vernetzung und Übernahme von Verantwortung in nationalen und internationalen Young Psychiatrists' Organisationen haben jungen Psychiatern ermöglicht, an Entscheidungsprozessen teilzuhaben und Rahmenbedingungen für ihre berufliche Entwicklung zu schaffen. Diese Arbeit beschreibt die Prinzipien und Ziele, die den existierenden Netzwerken nationaler und internationaler Young Psychiatrists' Organisationen zugrunde liegen. Es wird auf verschiedene Projekte im Bereich der Weiterbildung und Vernetzung näher eingegangen. Am Beispiel Kroatien wird die Rolle dieser Netzwerke für die Gründung nationaler Vereinigungen psychiatrischer Weiterbildungsassistenten aufgezeigt.
Keywords: Psychiatrist; trainees; psychiatry; education; organization; community networks; professional development